ANALISIS PEMUNGUTAN DAN PENCATATAN PAJAK BUMI DAN BANGUNAN PEDESAAN DAN PERKOTAAN (PBB - P2) PADA PEMERINTAH KABUPATEN MINAHASA TENGGARA - Langi, Lisa Tivani; Saerang, David P. E.; Warongan, Jessy D.L (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
At first PBB-P2 was levied by the central government. The transfer of UN-P2 in Southeast Minahasa district begins on January 1, 2014 and is expected to increase the Local Revenue (PAD) and at the same time improve the structure of Regional Revenue and Expenditure Budget (APBD), improve public services, accountability and transparency in the management of PBB-P2. The purpose of this study was to analyze how the collection and recording of PBB-P2 at the Government of South Minahasa District. The purpose of this research is to know and analyze the collection and recording of PBB-P2 in South Minahasa. The type of research used is descriptive qualitative research. The result of the research shows that the PBB-P2 collection in Southeast Minahasa Regency still has obstacles, namely Taxpayer Notification Name (SPPT) which isnât in accordance with the name of tax object, the existence of double SPPT, the SPPT but the location of the tax object is unknown, the lack of awareness in making the payment of PBB -P2 by taxpayers domiciled outside the region but has a tax object in the region. Recording of PBB-P2 revenue is still the difference between budget realization of PBB-P2. It is recommended that the Regional Finance Board of Southeast Minahasa hold socialization to local governments and local communities regarding the implementation of PBB-P2 collections, so that taxpayers have a concern in the case of PBB-P2 payments on time and active in reporting the object/subject of tax when there are problems encountered.Keywords : Collection, accounting records, PBB-P2